PENGARUH KUALITAS PELAYANAN DAN KETEPATAN PENGIRIMAN TERHADAP KEPUASAN PELANGGAN DALAM MENGGUNAKAN JASA PENGIRIMAN BARANG NINJA EXPRESS DI MASA PANDEMI COVID-19 - Saefur Rohman; Fino Wahyudi Abdul (Jurnal Logistik Indonesia, 2021)
The Effect of Service Quality and Delivery Accuracy on Customer Satisfaction in Using Ninja Express Freight Forwarding Services during the Covid-19 Pandemic, Saefur Rohman, NPM: CF116112019, This study aims to determine how much influence Service Quality and Delivery Accuracy have on customer satisfaction. The sample used in this study consisted of 60 respondents obtained through nonprobability sampling techniques. The method used was accidental sampling. The dependent variable in this study was Customer Satisfaction and the independent variables were Service Quality and Delivery Accuracy. The results of this study indicate that Service Quality and Delivery Accuracy simultaneously have an effect on Customer Satisfaction. This can be seen from the results of the f test which shows a significance value of 0.000 Ftable value of 3.16. This shows that H3 is accepted.